Real-World Evidence Studies of Oritavancin Use in Gram-Positive Infections Augment Randomized Controlled Trials to Address Clinical and Economic Outcomes - Redell, Mark (Drugs Real World Outcomes, 2020)
Randomized controlled trials (RCTs) sponsored by pharmaceutical manufacturers for regulatory approval are conducted with restrictive criteria in an effort to definitively demonstrate the safety and efficacy of a drug or biologic. Unfortunately, the strict enrollment criteria in RCTs may exclude patients likely to receive the medication in a real-world clinical practice. Antibiotic RCTs for registration are designed to show noninferiority against standard of care or best available therapy, often minimizing clinical differentiation needed by clinicians to select the optimal agent for their patients. Lastly, RCTs do not include pharmacoeconomic data that would add a cost basis for determining the value of one product over another. Real-world studies may add support to the safety and efficacy demonstrated from RCTs and address patient populations excluded from clinical development programs. This supplement presents several real-world studies demonstrating the clinical and economic outcomes of various uses of oritavancin to augment the evidence published from RCTs. Clinicians may decide how to use this information in their own practice settings.